Expressão de pistas e preocupações emocionais de pacientes com câncer em consultas médicas: um estudo sobre comunicação em oncologia - Romeiro, Fernanda Bittencourt (Universidade do Vale do Rio dos Sinos, 2019)
This dissertation is composed by two empiric articles from a research project, which assesses the physician-patient communication through patients’ cues and concerns and physicians’ responses to these emotional expressions during oncological consultations. In the first article, it was used the VR-CoDES (Verona Coding Definitions of Emotional Sequences) to describe both emotional cues/concerns expressed by patients during their oncological treatment and physicians’ responses toward such emotional expressions, from video recorded consultations. In the second article, the relation between patients’ emotional cues and concerns, physicians’ responses, socio-demographic and clinical variables, satisfaction and physician-patient communication was examined. First article design was mixed, descriptive and exploratory. Second article design was correlational. The participants were 12 patients with mean age of 63.25 years (SD = 15.70 years), eight women and four men, which were under cancer treatment for a mean period of 28.42 months (SD = 38.59 months), eight oncologists that attended the patients during their treatment. The instruments were questionnaires for socio-demographic data (professional and clinical); VR-CoDES (Verona Coding Definitions of Emotional Sequences); Satisfaction Inventory (translated and adapted from the PSIAQ - Patient Satisfaction with the Interview Assessment Questionnaire); and CAT – Communication Assessment Tool. In article 1, the results revealed that patients expressed 349 cues/concerns in 12 consultations. In response to the cue/concerns, 394 interventions of the physicians' answers were identified, being the most used were explicit (F = 135; 34.3%) and non-explicit (F = 111; 28.2%) responses both with reduce function. The cue most used by the patients referred to physiological concerns related to the disease and to the treatment. The results of article II indicated that explicit and reduce space responses were positively related to expressions of potentially stressful experiences for the patients, and content repetition at the patient's own initiative. The cue expressed through physiological symptoms was related to the physician's responses with proveder space only to the content. Patients expressed less nonverbal behaviors (eg crying, silence, or pauses in speech) as they were treated longer and more empathic responses were provided to these patients. There was no relation of cues patients' concerns and answers of the doctors with the satisfaction and evaluation of the communication. It is suggested that physicians be trained in communication skills in order to promote the recognition of patients' emotions and to provide emotional support in the context of oncology.
Keywords: Comunicação médico-paciente; Preocupações emocionais; Câncer; Physician-patient communication; Emotional concerns; Cancer; ACCNPQ::Ciências Humanas::Psicologia